Pendampingan Masyarakat dalam Pembuatan Aneka Cemilan Gula Merah Melalui Keterlibatan Mahasiswa sebagai Agen Wirausaha - Galib, Mukhtar; Syam, Jumiati; Muharram, Muharram; Gunawan, Aden (STIE Jambatan Bulan, 2026)
This community service program aims to enhance the skills of the residents of Bantimurung Subdistrict, Maros Regency, in processing palm sugar into various value-added snack products, while simultaneously preparing final-year university students as prospective independent entrepreneurs in the local food sector. The program was conducted in September 2025 through several stages, including training on the economic potential of palm sugar, demonstrations of caramelization techniques, hands-on production practice, and product quality evaluation. The activity involved local community members and fifteen final-year students who received training on entrepreneurship and basic food production techniques. The results indicate a significant improvement in the community’s ability to produce four types of snacks: palm sugar dodol, caramelized banana chips, caramelized peanuts, and palm sugar candy. The students also gained strengthened knowledge of simple business management, including cost of production calculation and basic marketing strategies. The collaboration between both groups created a productive learning environment and strengthened the community’s readiness to develop small-scale household businesses. This program provides positive contributions to enhancing local economic capacity while fostering a stronger entrepreneurial mindset among students